PHYSICIANS' ATTITUDES TOWARDS THE APPROACH TO DIABETIC NEUROPATHY IN PUBLIC AND PRIVATE HEALTH FACILITIES, 2023: ACTITUDES DE LOS MÉDICOS HACIA EL ABORDAJE DE LA NEUROPATIA DIABETICA EN ESTABLECIMIENTOS DE SALUD PÚBLICOS Y PRIVADOS, 2023 - Longa López, John Carlos Marcelino (2024)
ABSTRACT Objective: To describe the attitudes of doctors towards the approach to diabetic neuropathy.Methods: Descriptive, observational, cross-sectional and prospective study, sample of 143 doctors, non-probabilistic convenience sampling. The variables: years of professional practice, specialty, proportion of patients in the medical consultation with a diagnosis of diabetes mellitus (type 1 or 2), proportion of patients with diabetes mellitus with a diagnosis of diabetic neuropathy, attitudes towards the approach to diabetic neuropathy. A 5-category Likert scale was used to evaluate attitudes in 3 dimensions: prioritization, diagnosis and treatment. Descriptive statistics were used.Results: In the prioritization dimension, 57.4% prioritize metabolic control over the evaluation of complications. Diagnostic dimension: 80.5% of doctors surveyed rely on symptoms and signs reported by the patient to make the diagnosis of said complication, 66.5% recognize that they do not use an instrument for the evaluation of neuropathy and 39.9% would not use it either. had it. In the treatment dimension, 73.5% recognize that analgesic treatment for diabetic neuropathy is frustrating and 50.4% feel “afraid” to titrate the dose of anti-neuropathic analgesic medication due to adverse effects.Conclusions: The attitudes of doctors compromise different areas of the approach to diabetic neuropathy such as prioritization, diagnosis and treatment with a tendency to prioritize metabolic control and other microvascular complications, to under-diagnosis, to “under-treatment”. ” and the need to refer patients for specialized management.